Effects of combined aerobic-strength training and yoga on quality of life and related parameters in women with pituitary adenoma after surgery: a randomized crossover study. Issue 6 (2nd May 2022) - Dülger, Esra; Mut, Melike; Erbas, Tomris; Sahiner, Levent; Vardar Yağlı, Naciye; Bilgin, Sevil
Abstract: Objective: The pituitary gland is responsible for hormonal balance in the body, and disruption of hormonal balance in patients with pituitary adenoma (PA) indirectly affects the quality of life. This study aimed to examine the effects of yoga and combined aerobic and strength training (A+ST) on quality of life and related parameters such as sleep, fatigue, emotional state, sexual function, and cognitive status in women with PA. Design: Ten women with PA were included in this randomized crossover study. Group 1 ( n  = 5, mean age: 52 ± 13.5 years) received A+ST for the first 6 weeks, a 2-week washout period, and yoga for the second 6 weeks. Group 2 ( n  = 5, mean age: 41.8 ± 14 years) received the yoga program first, followed by the A+ST program. Methods: Participants were assessed using the following tools before and after each exercise intervention: Functional Assessment of Cancer Therapy–Brain (FACT-Br) (quality of life), Pittsburg Sleep Quality Index, Fatigue Severity Scale (FSS), Female Sexual Function Index (FSFI), Hospital Anxiety and Depression Scale (HADS), and Montreal Cognitive Assessment Scale (MOCA). Results: FACT-Br scores were higher after the yoga program, HADS anxiety score was lower after the A+ST program, and MOCA scores increased after both exercise programs ( P   < 0.05). FSS score decreased after both exercise programs, but not significantly. In addition, nonsignificant decreases in HADS anxiety and depression scores and increased FSFI scores were observed after the yoga program. Conclusion: A+ST and yoga have positive effects on the quality of life in PA. We recommend yoga and A+ST as a supportive therapy for this population that may face comorbidities after surgical and medical treatment. Our results indicate these patients may benefit from physiotherapist-guided exercise programs.